2014
DOI: 10.1186/1471-2253-14-41
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective derivation and validation of a search algorithm to identify extubation failure in the intensive care unit

Abstract: BackgroundDevelopment and validation of automated electronic medical record (EMR) search strategies is important in identifying extubation failure in the intensive care unit (ICU). We developed and validated an automated search algorithm (strategy) for extubation failure in critically ill patients.MethodsThe EMR search algorithm was created through sequential steps with keywords applied to an institutional EMR database. The search strategy was derived retrospectively through secondary analysis of a 100-patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…We excluded patients who required MV for <48 h. This lends the study to potential selection bias. However, patient intubated for short duration are at minimal risk for extubation failure [25], and previous studies investigating extubation failure have used different cutoffs (12-48 h) to exclude patients who are placed on MV for completely reversible causes [11,35]. Additionally, our study did not control for the type of acute neurologic illness which almost certainly impacts extubation rates and prognosis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We excluded patients who required MV for <48 h. This lends the study to potential selection bias. However, patient intubated for short duration are at minimal risk for extubation failure [25], and previous studies investigating extubation failure have used different cutoffs (12-48 h) to exclude patients who are placed on MV for completely reversible causes [11,35]. Additionally, our study did not control for the type of acute neurologic illness which almost certainly impacts extubation rates and prognosis.…”
Section: Discussionmentioning
confidence: 92%
“…Details of this search strategy have been described elsewhere [11]. Briefly, data from the Mayo Clinic Life Sciences System [12], an exhaustive database of patient information which has been validated [13,14], was accessed using a Web-based commercial software tool set [Data Discovery and Query Builder (DDQB); International Business Machines Corp] [15].…”
Section: Automated Electronic Strategy For Identifying Extubation Faimentioning
confidence: 99%
“…With the widespread adoption of the use of EHR, electronic search strategies have increased in frequency [6]. Automated search strategies have shown high sensitivity and specificity in recognizing various medical entities [6,7]. These strategies would help to accurately identify any risk factors documented in the EHR, contribute to the utilization of various quality improvement initiatives, reduce the incidence of manual errors, and hence reduce the cost and enhance the effectiveness of medical care.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, electronic search strategies provide an added value to highly efficient data extraction within an electronic medical environment and allow rapid and more accurate analysis of large databases. [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, search algorithms have been successfully developed for extracting information on Charlson comorbidities [2], initiation of emergent intubations in the intensive care unit (ICU) [4], extubation time in the ICU [5], risk factors for acute lung injury [6], and chronic co-morbidity phenotypes from the EMR and Genomics studies [7]. These studies have all demonstrated that electronic searches can achieve sensitivities and specificities greater than 90% when compared to manual search efforts.…”
Section: Introductionmentioning
confidence: 99%